2010
DOI: 10.1007/s12247-010-9075-1
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopy for the In-Line Characterization of Powder Voiding Part II: Quantification of Enhanced Flow Properties of Surface Modified Active Pharmaceutical Ingredients

Abstract: In this work, dry-particle coating was used to modify the surface properties of active pharmaceutical ingredients (APIs) having extremely poor flow properties. Near-infrared (NIR) spectroscopy was utilized as a novel approach to characterize the improved flow behavior of APIs and their blends. Acetaminophen and ibuprofen were coated with nano-sized silica at two different coating levels (0.5% and 1% w/w of the API) in dry-particle coating devices viz. magnetically assisted impaction coater (MAIC) and Hybridize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 28 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Similar to the current results, previous studies have demonstrated that in some cases, the addition of nano-silica particles through low intensity methods (i.e. hand mixing or v-blending) can offer substantial flow improvements, although high intensity dry 13 coating performed by MAIC [24,[30][31][32][33][34], LabRAM [26], or Fluid Energy Milling [6,27] leads to better improvements. As mentioned before, Yang et al proposed that the flow improvements were due to the introduction of nano-sized surface asperities in the form of the guest particle [24].…”
Section: Powder Flow and Fluidization Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar to the current results, previous studies have demonstrated that in some cases, the addition of nano-silica particles through low intensity methods (i.e. hand mixing or v-blending) can offer substantial flow improvements, although high intensity dry 13 coating performed by MAIC [24,[30][31][32][33][34], LabRAM [26], or Fluid Energy Milling [6,27] leads to better improvements. As mentioned before, Yang et al proposed that the flow improvements were due to the introduction of nano-sized surface asperities in the form of the guest particle [24].…”
Section: Powder Flow and Fluidization Characterizationsupporting
confidence: 88%
“…Several methods have been developed to achieve high quality surface coatings in a dry process [6,[23][24][25][26][27][28][29]. These methods have been shown to offer substantial flow improvements by simultaneously deagglomerating the cohesive nano-silica, i.e., glidant powders, and dispersing the nano-silica particles across the host or carrier particle surface, which include Magnetically Assisted Impaction Coating [24,[30][31][32][33][34], Acoustic Mixing [26], and Fluid Energy Milling [6,27]. Yang et al derived a simple equation that showed that the reduction in cohesion due to the introduction of the nano-sized surface asperity in the form of the nanosilica coating is inversely proportional to particle size [24], hence coating of nano-silica would lead to improvements in the flow properties.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal silicon dioxide (SiO 2 ) was placed over the ibuprofen along with a portion of preweighed lactose in order to prevent the cohesive mixture from sticking to the sieve. Components were rubbed together through the sieve [13]. This preliminary mixture was used as the API preblend.…”
Section: Preparation Of Calibration and Validation Blendsmentioning
confidence: 99%
“…The Hybridizer from Nara Machinery is a high energy mixer that has been often used in the literature to carry out dry coating [2][3][4].…”
Section: Processmentioning
confidence: 99%